The Spanish economy, 1959-1976 - Wright, Alison (London : Macmillan, 1977)
In tis book the author dealt with agrarian and industrial structure, communication and foreign trade partners are all dealt with. The labour situation is touched, some acute comments are made about education. The most helpful chapters are about banking, credit, and the government's fiscal and monetary policy. Which shows how limited were the real controls that policy makers were able to exercise over the economy during this period.
Includes bibliographical references and index.
aia 27/09/2017
Loans
Keywords: Spain -Economic condition; Spain